Evaluation of mahua oilcake (Bassia latifolia Roxb.) as a non-conventional feed ingredient for Labeo rohita (Ham.) fingerlings - Rath, S. C.; Nayak, K. C.; Mohanty, T. K.; Devraj, C.; Chandan, N. K.; Mohanta, K. N.; Giri, S. S. (Indian Journal of Fisheries, 2017)
Mahua (Bassia latifolia Roxb.) oil cake (MOC) is rich in protein (24%) and energy (19.0 KJ g-1) with high levels of fatty acids comprising saturates (45%), monoenes (42%) and polyunsaturated fatty acids (PUFA, n-6) (7%). Saponin, phenol and flavonoids are the main metabolites. Labeo rohita (Hamilton, 1822) fingerlings (5.25Â±0.2 g) were fed with five iso-nitrogenous (28% CP) diets containing MOC at 0% (F1), 10% (F2), 20% (F3), 30% (F4) and 40% (F5) for 90 days in 300 l cement cisterns. Survival (%) of all groups were statistically similar (p>0.05). Weight gain (%) and specific growth rate (SGR) were significantly lower in F1, F2, F5 and higher in F3 and F4 groups (p